Evaluation of Escherichia coli inactivation and sunlight penetration in a shallow maturation pond: hydrodynamics and disinfection - Daniel Filipe Cristelo Dias (2016)
Maturation ponds can be used as post-treatment of anaerobic and aerobic reactors. They are widely used post-treatment units for treating wastewater in developing countries like Brazil because of their robustness and low implementation and operation costs, as well as being effective in removing pathogens and nitrogen. For this research, a natural wastewater treatment line was proposed to treat raw sewage, using a total area of 1.5 m2/inhab., while maintaining high removal efficiencies for the major constituents. In order to reduce the required area, an upflow anaerobic sludge blanket (UASB) reactor, a pond without baffles followed by another shallow pond (44 cm) with baffles was proposed. A rock filter with three decreasing grain sizes was also incorporated into the system after the ponds in series to remove the remaining particulate organic matter from the ponds. The system was designed to treat sewage of 250 inhabitants. This study aimed to evaluate the performance of the new treatment line, with special attention on the removal of coliforms and mechanisms associated with ultraviolet (UV) radiation. The results of the monitoring period for the whole system were very positive for BOD and COD removal, with average removal efficiencies of 92.6% and 79.4%, respectively, and excellent E. coli removal efficiency (6.1 log units). Solar radiation was measured at the surface and various levels within the second pond to determine extinction depths. UV-A and UV-B waves only reached a maximum of 10 cm and photosynthetically active radiation (PAR) penetrated up to 30 cm. Models to estimate PAR attenuation were also estimated and correlated with turbidity. E. coli inactivation profiles regarding depth were performed in batch tests using quartz tubes inserted at different levels within the pond for two different periods of the day (morning and afternoon). The E. coli inactivation rate decreased with increasing depth, and at deeper depths, inactivation in the morning was greater. Dark inactivation showed to have little overall influence, but both repair and the decay occurred. A simple model for the decrease of the inactivation coefficient with depth was incorporated into the dispersed flow model, and allowed very good fittings with the effluent E. coli concentrations monitored at both ponds. The applied and received doses of UV and PAR were estimated regarding the inactivation coefficient. Vertical baffles were inserted in the second pond to increase E. coli inactivation, and results indicated that improvements were achieved with this modification.